Clinicopathologic features of undetected dysplasia found in total colectomy or proctocolectomy specimens of patients with inflammatory bowel disease. Issue 2 (10th May 2022) - Bahceci, Dorukhan; Lauwers, Gregory Y; Choi, Won‐Tak
Abstract : Aims: It remains controversial as to whether targeted biopsies should completely replace random biopsies for dysplasia surveillance in patients with inflammatory bowel disease (IBD). Several histologic patterns of nonconventional dysplasia have been described in IBD. This study aimed to investigate the rate and clinicopathologic features of dysplastic lesions found in total colectomy or proctocolectomy specimens that were undetected on prior colonoscopy. Methods and results: The study analyzed 207 consecutive IBD patients who underwent a total colectomy or proctocolectomy and had at least one high‐definition colonoscopy prior to colectomy. Dysplasia found in the colectomy specimens was classified as undetected, only when there was no corresponding site of dysplasia detected on previous colonoscopic biopsies. Twenty‐seven (13%) patients had 49 undetected dysplastic lesions found only at colectomy, while 22 (11%) had 31 previously detected dysplastic lesions only. The remaining 158 (76%) patients had no dysplasia. A greater proportion of the undetected (19%) or previously detected (23%) dysplasia group had concurrent primary sclerosing cholangitis compared with only 3% in the group without dysplasia ( P  < 0.001). The undetected dysplastic lesions were more likely to have nonconventional dysplastic features (76%), low‐grade dysplasia (94%), and a flat/invisible gross appearance (73%) compared with the previously detected dysplastic lesions (13%, 68%, and 48%, respectively) ( P  < 0.05). Almost all patients with undetected dysplasia (93%) had a colonoscopy within 1 year of colectomy. Conclusion: The rate of undetected dysplasia is not insignificant (13%), suggesting that increased random biopsies may improve the rate of dysplasia detection, including nonconventional dysplasia. Abstract :